2011
DOI: 10.1063/1.3664855
|View full text |Cite
|
Sign up to set email alerts
|

A resonant two body system for a point absorbing wave energy converter with direct-driven linear generator

Abstract: Wave power calculations for a wave energy conversion device connected to a drogue Journal of Renewable and Sustainable Energy 6, 013117 (2014) Based on an earlier conceptual model of a two body system point absorbing wave energy converter tuned to resonance in Swedish west coast sea states, an extended coupled hydrodynamic, mechanic, and electromagnetic model has been developed. The hydrodynamic characteristics of the two body system are studied in the frequency and time domain, while its response to real Swed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 17 publications
2
42
0
Order By: Relevance
“…As the wave period increases, the capture width ratio decreases, much more rapidly than in the single body system. This was already observed by Engström [39].…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…As the wave period increases, the capture width ratio decreases, much more rapidly than in the single body system. This was already observed by Engström [39].…”
Section: Resultssupporting
confidence: 71%
“…Ideally, a different body size should be selected for each study location, to match the local wave climate. In this analysis, following Engström et al [38,39], a spherical body was added as the submerged object, in order to modify the natural frequency of the system. The calculations showed that for the least energetic sites (Crotone, Monopoli, Catania, Ortona), the maximum power output is obtained when the system resonates with waves with peak periods of 5.5 s, while at the most energetic sites (Alghero, Mazara del Vallo, Ponza and La Spezia), the optimum natural period of oscillation ranges between 6 and 7 s. More specifically, it is 7 s at Alghero, 6.5 s at Mazara del Vallo and La Spezia and 6 s at Ponza.…”
Section: Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This WEC concept has been validated by theory and extensive real sea trials [9,10]. Early studies indicate how the power output of the WEC is influenced by the sea state, buoy characteristics and PTO damping [11][12][13]. The first is given by the chosen location, but the other two can be altered and optimized in the mechanical design and dimensioning of the buoy and the choice of generator type and load connection.…”
Section: Open Accessmentioning
confidence: 99%
“…10,11 The researchers at the Swedish Centre for Renewable Electric Energy Conversion at Uppsala University started a wave energy project in 2002. [12][13][14][15][16] This project develops a WEC of point absorber type with a direct-driven linear generator as power take-off (PTO). A buoy located at the ocean surface is connected to a linear generator placed on the seabed via a line.…”
Section: Introductionmentioning
confidence: 99%